Pengaruh Gaya Belajar dan Motivasi Belajar terhadap Hasil Belajar Siswa - Hadaniah; Mustafa; Syamsu A Kamaruddin (STKIP Subang, 2025)
This study aims to analyze and synthesize empirical findings on the partial and simultaneous effects of learning styles and learning motivation on student learning outcomes. Learning achievement is a key indicator of educational success, yet disparities in outcomes remain. These gaps may be linked to limited understanding of diverse learning styles visual, auditory, and kinesthetic as well as fluctuations in student motivation. Thus, this review provides an updated and comprehensive overview of the roles of these internal factors and examines the consistency of previous research. Findings show that the influence of learning styles varies across studies. Some research reports that aligning learning styles with instructional methods improves outcomes, such as increases of 15% for visual learners and 20% for kinesthetic learners. However, other studies find no significant impact, likely due to external factors in the learning environment. In contrast, learning motivation consistently demonstrates a positive and significant effect on learning outcomes, functioning as a psychological driver that supports sustained learning behavior. Simultaneously, learning styles and learning motivation together have a significant effect on learning outcomes. Their interaction indicates that high motivation can compensate for less optimal learning styles, while appropriate learning styles can enhance intrinsic motivation. The combined contribution of both variables can reach about 25.4%, with the remainder influenced by other factors. To improve learning outcomes, teachers should adopt multimodal instructional strategies and strengthen intrinsic motivation through constructive feedback and supportive classroom conditions. Keywords: Learning Styles, Learning Motivation, Learning Outcomes, Visual, Auditory, Kinesthetic.